Anggaran Pendidikan Pasca Amandemen UUD 1945 - Edy Suandi Hamid (Universitas Islam Indonesia, 2003)
The fundamental problem that emerges the controversy relating to amendment the article 31 verse 4 regarding the budget of education. The article 31 verse 4 contains that the budget of national education either taken from national state budget or prov ince budget at least 20%. After conducting amendment and it is not implement raises many questions and many interpretations on 20 %. To solve the problem it is better to formulate rigid interpretation. This important to do because of either the implementation as soon as possible or the target that will be conducted step in step.